Neurophysiological Effects of the Anterior Cingulate Cortex on the Exacerbation of Crohn’s Disease: A Combined fMRI-MRS Study - Kong, Ning; Gao, Chen; Zhang, Fan; Zhang, Meng; Yue, Juan; Lv, Kun; Zhang, Qi; Fan, Yihong; Lv, Bin; Zang, Yufeng; Xu, Maosheng (Frontiers in Neuroscience, 2022)
Background: Crohn’s disease (CD) is characterized by repetitive phases of remission and exacerbation, the quality of life of patients with CD is strongly influenced by disease activity, as patients in an active phase experience significantly worse symptoms. To investigate the underlying mechanism of how the course of CD is exacerbated based on the bi-directionality of the brain-gut axis (BGA), we conducted a multi-modality neuroimaging study that gets resting-state functional magnetic resonance imaging (rs-fMRI) combined with proton magnetic resonance spectroscopy (MRS) to detect abnormalities in the anterior cingulate cortex (ACC). Material and methods: We made a comparison between CD patients in active/remission phase and healthy controls (HCs), not only employed an innovative wavelet-transform to analyze the amplitude of low frequency fluctuation (ALFF) but also compared the sensitivity of wavelet-transform and the traditional fast Fourier transform (FFT). Brain metabolites such as glutamate (Glu), myo-inositol (mIns) and gamma-aminobutyric acid (GABA) were also detected. Then correlation analysis was made to see whether changes in the ACC correlates with CD’s clinical symptoms. Results: We found that wavelet-transform is slightly more sensitive. Patients in the active phase exhibited higher mWavelet-ALFF/mALFF in the left ACC and the left superior medial frontal cortex (SMFC). Patients in the active phase showed increased Glu levels in the ACC than patients in the remission phase or HCs (p=0.039 and 0.034 respectively). Clinical scores, including Visual Analogue Scale (VAS) and the Hospital Anxiety Depression Scale (HADS), showed the degree of abdominal pain in the active group was higher (p = 0.025), patients in the active phase were more anxious and depressed than patients in remission or HCs (all p＜0.05). There were positive correlations between mWavelet-ALFF values of the ACC and HADS-depression scores (r = 0.462, p = 0.006). Besides, concentrations of Glu positively correlates with mWavelet-ALFF in the ACC (r = 0.367, p = 0.006). Conclusion: Abnormal spontaneous activity and metabolites in the ACC, along with inflammation, pain, and psychological disorders, may contribute to the exacerbation of CD and interact with each other. Therefore, the ACC might be a potential neural alternative for managing the exacerbation of CD.